Influence of water activity on the enantioselective esterification catalysed by hydrogel immobilised lipase from candida rugosa / Aiza Harun - Harun, Aiza (Universiti Teknologi MARA Cawangan Pahang, 2006)
Lipase from Candida rugosa was immobilised onto N-vinyl-2pyrrolidone- co-styrene (VP-co-ST) hydrogel. The ethylene dimethacrylate (EDMA) and azoisobutyronitrile (AIBN) were used as a cross-linking agent and polymerization promoter respectively. This particular VP-co-ST hydrogel immobilised lipase was used to catalyse the enantioselective esterification of (R,S) -2-(4chlorophenoxy) propanoic acid with n-tetradecanol. Only VP-coST hydrogel immobilised lipase with composition of VP 10% and ST 90% and native lipase (unimmobilised lipase) will be discussed in this study. The reaction was performed at optimum reaction time of 24 hours and at optimum temperature 40"C in organic media. The study revealed that water activity, a iv may influence the enantioselective esterification in which at lower a value, the percentage of ester conversion was greater compared with at higher all' value when using both hydrogel immobilised lipase and native lipase in the reaction. However, when comparing between these two lipases, the hydrogel immobilised lipase exhibited higher percentage of ester conversion rather than native lipase at optimum water activity value of 0.3.